2021
DOI: 10.1213/xaa.0000000000001491
|View full text |Cite
|
Sign up to set email alerts
|

Rocuronium-Induced Dilated Nonreactive Pupils in a Patient With Coronavirus Disease 2019: A Case Report

Abstract: We report the clinical case of a patient with coronavirus disease 2019 (COVID-19) who had recently undergone neurosurgery and presented with dilated nonreactive pupils during continuous rocuronium infusion, which was reversible with the suspension of the drug. Both the neurosurgical procedure and possible disruption of the blood–brain barrier due to COVID-19 infection may have led to the action of rocuronium in the central nervous system (CNS). Thus, clinicians must remember that neuromuscular blocking agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Several reports have described that neurological symptoms, such as meningitis and encephalopathy, occur after COVID-19 infection, even with a negative spinal fluid SARS-CoV-2 PCR test [ 11 13 ]. In fact, a case of pupil dilatation caused by the muscle relaxant rocuronium has been reported in a patient with COVID-19 [ 14 ]. Normally, rocuronium does not pass through the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described that neurological symptoms, such as meningitis and encephalopathy, occur after COVID-19 infection, even with a negative spinal fluid SARS-CoV-2 PCR test [ 11 13 ]. In fact, a case of pupil dilatation caused by the muscle relaxant rocuronium has been reported in a patient with COVID-19 [ 14 ]. Normally, rocuronium does not pass through the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…After the observation of this finding, rocuronium infusion was terminated and the pupil size and reactions returned to normal approximately after 12 hours. 12 Sugammadex is a newly developed pharmacological agent to reverse the neuromuscular blockade. It forms stable complexes with steroidal NMBAs, particularly with rocuronium.…”
Section: Discussionmentioning
confidence: 99%
“…Drug-related pupil dilation is also a common factor, and numerous drugs can disrupt the balance of the sympatheticsystem, influencing pupil size to varying degrees. Sympathetic-activated medicines, such as adrenalin, norepinephrine, and ephedrine, can excite the sympathetic nervous system, directly leading to mydriasis 9 ; atropine, scopolamine, and ipratropium can antagonize the function of the vagus nerve to induce dilation of pupils [14][15][16][17] ; papaverine, as an opioid derivative, is mainly used to resist against vasospasm in clinic, whereas Zhou et al 18 reported that its toxic and side effects could also lead to transient dilatation of pupils; studies demonstrated that anesthetics, such as propofol and rocuronium, may also cause dilation of pupils in some patients 19,20 ; for instance, in 2017, Korf et al 21 reported a case of transient dilated pupils caused by inhalation of the sevoflurane. Sevoflurane, propofol, and rocuronium were all used in both cases.…”
Section: Anestheticsmentioning
confidence: 99%